Morphology of Selected Trunk Muscles of a Gibbon - Malinowski, Andrzej; Jakubowicz, Marian; Marecki, Bogusław (Anthropological Review, 1977)
The paper presents results of examination of selected muscles of a six years old female gibbon Hylobates lar. Descriptive traits as well as metric characters and quotient indices arc considered. These data are compared with respective information on human aduits and fetuses as well as on other primates. Detailed characteristics are given for following muscles: m. sternocleidomastoid, m. pectoralis major, m. pectoralis minor, m. serratus anterior, m. trapezius, m. latissimus dorsi and m. rhomboideus.